TREATMENT OF HUMAN RESOURCES ACCOUNTING AT PT.POS INDONESIA - Rahim, Rahmatika; Semaun, Syahriyah; Purnamasari, Rini (Islamic Financial And Accounting Review, 2025)
This research is motivated by the importance of the role of human resources in company operations and the need for proper accounting records of related costs. PT Pos Indonesia as a state-owned company engaged in logistics and financial services has complexities in human resource management. The purpose of this study is to find out how accounting treats human resource costs and how they are recognized in the company's financial system, especially in PT Pos Indonesia Parepare Branch. This research method is classified as a qualitative research method, meaning that this research seeks to describe, record, analyze, and explain what is researched through observation, interviews, and documentation research. This research approach is a case study, the type of research carried out is Field Research (field research). The results of the study show that the accounting treatment of human resources at PT Pos Indonesia is carried out through recording costs as an expense in the income statement. The Company does not recognize human resources as assets in its financial statements, but manages them strategically through periodic performance appraisal policies, online training through internal applications, and AKHLAK value-based work discipline development. Thus, the approach used is expense-based, but the company still views HR as an important factor in operational success. Although PT Pos Indonesia is not an Islamic financial institution, in practice it still pays attention to the principles of sharia principles, such as transparency, fairness, and the separation of social funds from the company's operational funds. These values are in line with the principles of sharia accounting as contained in the QS. Al-Baqarah verse 282 which emphasizes the importance of recording and justice in muamalah. Thus, human resource accounting at PT Pos Indonesia demonstrates the integration between professional practice and ethical values in Islam.